Validity and Reliability of the Turkish Version of the Environmental Health Literacy Scale. - Akgül Gündoğdu, Nurcan; Selçuk Tosun, Alime; Dağcı Günal, Büşra (Journal of Evaluation in Clinical Practice, 2025)
Aim: This study aimed to translate the Environmental Health Literacy Scale (EHLS) into Turkish and assess its construct validity and internal consistency. Methods: This research employs a methodological design. The research was conducted during the 2022–2023 academic year with a sample of 500 students from the Faculty of Health Sciences. The data were collected via the introductory information form, the EHLS, and the Environmental Awareness Scale of university students. Subsequently, the data were transferred to the IBM SPSS Statistics 23 and IBM SPSS AMOS 23 software programs. Upon evaluation of the research data, frequency distributions for categorical variables and descriptive statistics for numerical variables were provided. Content validity was evaluated through the acquisition of expert approval. Confirmatory factor analysis was employed for scale validity, while Cronbach's α, test–retest and parallel form analyses were utilized for reliability. Results: The content validity index of the scale was determined to be 1.00. The scale is constituted of four discrete scales (general, food, air and water), each comprising three dimensions. In consideration of the fit indices, specifically the χ2/df, GFI, TLI, IFI, CFI, RMSEA and SRMR, it can be concluded that the general, food, air and water scales are deemed acceptable. Cronbach's α coefficients for the scales were found to be 0.70, 0.81, 0.83 and 0.79, respectively. In the parallel form analysis, a statistically significant positive relationship was identified between the scales. Conclusions: The findings of this research indicate that the scale is a reliable instrument for assessing the environmental health literacy levels of undergraduate students enrolled in health sciences programs. It is anticipated that the scale will contribute to the advancement of environmental health literacy awareness.